Beneficial effects of natural phenolics on levodopa methylation and oxidative neurodegeneration - Kang, Ki Sung; Yamabe, Noriko; Wen, Yujing; Fukui, Masayuki; Zhu, Bao Ting (ELSEVIER SCIENCE BV, 2013)
Levodopa (L-DOPA) is widely used for symptomatic management in Parkinson's disease. We recently showed that (-)-epigallocatechin-3-gallate, a tea polyphenol, not only inhibits L-DOPA methylation, but also protects against oxidative hippocampal neurodegeneration. In the present study, we sought to determine several other common dietary phenolics, namely, tea catechins [(+)-catechin and (-)-epicatechin] and a representative flavonoid (quercetin), for their ability to modulate L-DOPA methylation and to protect against oxidative hippocampal injury. A combination of in vitro biochemical assays, cell culture-based mechanistic analyses, and in vivo animal models was used. While both tea catechins and quercetin strongly inhibit human liver catechol-O-methyltransferase (COMT)mediated O-methylation of L-DOPA in vitro, only (+)-catechin exerts a significant inhibition of L-DOPA methylation in both peripheral compartment and striatum in rats. The stronger in vivo effect of (+)-catechin on L-DOPA methylation compared to the other dietary compounds is due to its better bioavailability in vivo. In addition, (+)-catechin strongly reduces glutamate-induced oxidative cytotoxicity in HT22 mouse hippocampal neurons in vitro through inactivation of the nuclear factor-kappa B signaling pathway. Administration of (+)-catechin also exerts a strong neuroprotective effect in the kainic acid-induced oxidative hippocampal neurodegeneration model in rats. In conclusion, (+)-catechin is a dietary polyphenolic that may have beneficial effects in L-DOPA-based treatment of Parkinson patients by inhibiting L-DOPA methylation plus reducing oxidative neurodegeneration. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: CATECHOL-O-METHYLTRANSFERASE; RESERPINE-TREATED RAT; PARKINSONS-DISEASE; L-DOPA; TEA CATECHINS; HIPPOCAMPAL-NEURONS; HEALTHY-VOLUNTEERS; KAPPA-B; PLASMA; 3-O-METHYLDOPA